Investigations on the natural and acquired resistance of cattle to artificial infection with Cowdria ruminantium - du Plessis, J L; Bezuidenhout, J D (Journal of the South African Veterinary Association, 1979)
Sixty cattle, artificially immunized against C. ruminantium, were challenged 3, 6, 12 and 24 months later. Levels of conglutinin were determined in pre-immunization serum samples. There appeared to be a relationship between the pre-infection levels of conglutinin and the susceptibility of the animals to heartwater: At the time of immunization 31 out of 60 cattle (51,6%) with levels in the low-titre range (1:100-1:160) showed a typical febrile response, whereas 29 (48,4%) with conglutinin levels in the high-titre range (1:320 and higher) were either fully or partially resistant. Except for 2 animals that developed mild febrile reactions when they were challenged 2 years after artificial immunization, all the cattle were fully resistant to challenge with C. ruminantium infected sheep blood. It can be concluded that in this experiment cattle retained their immunity to heartwater for at least 2 years in the absence of reinfection.